Low-temperature-resistant electrolyte, preparation method and lithium ion battery
By using a composite solvent of cyclic carbonate solvents, chain carbonate solvents and carboxylate solvents in the lithium-ion battery electrolyte, as well as a dual-salt system of lithium hexafluorophosphate and lithium difluorosulfonimide in the lithium-ion battery electrolyte, the problem of performance degradation of lithium-ion batteries in the low-temperature environment is solved, the high conductivity of the electrolyte and the lithium-ion movement rate are achieved, and the low-temperature cycling performance of the battery is improved.
Patent Information
- Application Number
- CN202411905487.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-18
AI Technical Summary
The performance of lithium-ion batteries in low temperature environments has significantly declined, resulting in a decrease in the capacity and voltage of the battery below 20℃, a decrease in the conductivity of the electrolyte, and slow down the migration of lithium ions, making it easy to form dendrites or dead lithium.
Develop a low-temperature resistant electrolyte, using a composite solvent of cyclic carbonate solvent, chain carbonate solvent and carboxylic acid ester solvent, combining a double-salt system of lithium hexafluorophosphate and lithium difluorosulfonimide, and adding an appropriate amount of additives to improve the intercalation kinetics of lithium ions.
The conductivity and lithium ion movement rate of the electrolyte in a low temperature environment are improved, the electrolyte concentration polarization is reduced, the uniformity of lithium embedded reaction in the electrode thickness direction is improved, the risk of lithium extraction is reduced, and the thermal stability, hygroscopicity and compatibility of the electrolyte are ensured.
Smart Images

Figure CN119650864A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of battery electrolytes, and in particular to low-temperature resistant electrolytes, preparation methods and lithium-ion batteries. Background Art
[0002] In order to mitigate the energy crisis and the environmental impact of the fossil fuel-based economy, energy storage technology has become an important part of the current energy strategy. Lithium-ion batteries are a promising energy storage device with many advantages, such as high energy density, portability, lightness, flexibility and long service life. Lithium-ion batteries have been successfully commercialized and used in mobile phones, laptops, hybrid vehicles and electric vehicles.
[0003] However, the performance of lithium-ion batteries obviously declines at low temperatures, which limits their application. Below 20°C, the process of lithium ions embedding into electrodes is more difficult than the process of lithium ions escaping. When the operating temperature is below 0°C, the capacity and voltage drop significantly. Solid materials cannot escape the shackles of "thermal expansion and contraction". Ions are neither easy to embed nor to escape, and it is difficult to pass through the diaphragm. The viscosity of liquid materials increases or even solidifies at low temperatures, and the mass transfer process of charged particles and the speed of electrochemical reactions decrease accordingly. The compatibility of various components of lithium-ion batteries is greatly reduced at low temperatures.
[0004] Lithium-ion batteries work at low temperatures, and the discharge platform and capacity of the battery show a significant downward trend as the test temperature drops. In low temperature environments, especially below -20°C, the conductivity of the electrolyte decreases significantly, the resistance to charge transfer inside the battery increases, and the migration of lithium ions slows down, making it impossible for them to be embedded in the negative electrode in time during the charging process, which not only causes irreversible capacity loss of the battery but also easily forms dendrites or dead lithium on the surface of the negative electrode. Summary of the invention
[0005] In order to solve at least one of the above technical problems, a lithium-ion battery suitable for use in low-temperature environments is developed. The present application provides a low-temperature resistant electrolyte, a preparation method and a lithium-ion battery.
[0006] In one aspect, the present application provides a low-temperature resistant electrolyte, comprising a solvent and an electrolyte;
[0007] The solvent comprises 25-35 wt% of a cyclic carbonate solvent, 15-25 wt% of a chain carbonate solvent, and 45-55 wt% of a carboxylate solvent;
[0008] The electrolyte comprises a lithium salt and an additive; wherein the lithium salt is one or a combination of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide, and the concentration of the lithium salt is 0.8-1.2 mol / L; wherein the content of the additive is 1-3 wt%.
[0009] Optionally, the cyclic carbonate is ethylene carbonate, propylene carbonate or a combination of both.
[0010] Optionally, the chain carbonate is one or more of dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate and methyl propyl carbonate.
[0011] Optionally, the carboxylic acid ester is ethyl propionate.
[0012] Optionally, the lithium salt is a combination of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide.
[0013] Optionally, in the lithium salt, the weight proportion of lithium hexafluorophosphate is 4 / 11 to 7 / 11, and the weight proportion of lithium bis(fluorosulfonyl)imide is 4 / 11 to 7 / 11.
[0014] Optionally, the additive is one or more of vinylene carbonate, fluoroethylene carbonate, vinyl sulfate, and N,N-dimethyltrifluoroacetamide.
[0015] In a second aspect, the present application provides a method for preparing the above-mentioned electrolyte, wherein the various solvents are mixed evenly according to the formula amount, and then the formula amount of lithium salt is added. After the electrolyte is completely dissolved, the formula amount of additives is added, and the mixture is stirred and mixed evenly to obtain the electrolyte.
[0016] Optionally, the test is performed in an environment where the water oxygen content is less than 0.3 ppm.
[0017] In a third aspect, the present application provides a lithium-ion battery using the above-mentioned electrolyte.
[0018] In summary, the present invention includes at least one of the following beneficial technical effects:
[0019] 1. Using cyclic carbonate solvents, chain carbonate solvents and carboxylic acid ester solvents as composite solvents to improve the conductivity of the electrolyte and the lithium ion mobility in a low temperature environment;
[0020] 2. Using double salt to replace the traditional single salt electrolyte system can not only reduce the concentration polarization of the electrolyte, improve the uniformity of the lithium insertion reaction in the thickness direction of the electrode, reduce the risk of lithium precipitation, but also ensure the thermal stability, hygroscopicity and compatibility of the electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The conductivity of the electrolytes prepared in Examples 1 to 6 and Comparative Example 1 at different temperatures. DETAILED DESCRIPTION
[0022] In the prior art, when lithium-ion batteries are placed in a low temperature environment, the internal charge transfer resistance of the battery is large and the migration of lithium ions slows down, which can easily cause energy dendrites or dead lithium on the negative electrode surface.
[0023] The present application designs a low-temperature resistant electrolyte, including a solvent and an electrolyte; the solvent includes 25-35wt% of a cyclic carbonate solvent, 15-25wt% of a chain carbonate solvent, and 45-55wt% of a carboxylate solvent; the electrolyte includes a lithium salt and an additive; the lithium salt is one or a combination of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide, and the concentration of the lithium salt is 0.8-1.2 mol / L; the content of the additive is 1-3wt%.
[0024] The above electrolyte is prepared by mixing various solvents in a formula amount, then adding a formula amount of lithium salt, and after the electrolyte is completely dissolved, adding a formula amount of additives, stirring and mixing, and obtaining an electrolyte.
[0025] The present application also provides a lithium-ion battery prepared using the above-mentioned electrolyte.
[0026] The inventors have developed and designed ionic liquids using the advantages and characteristics of ionic liquids, and applied them to lithium-ion battery electrolytes, which have a positive effect on improving the low-temperature performance of lithium-ion batteries. By improving the formula of the electrolyte, adjusting the selection and ratio of cyclic carbonate solvents, chain carbonate solvents and carboxylic acid ester solvents, and selecting double salts (lithium hexafluorophosphate + lithium bis(fluorosulfonyl)imide) to replace the traditional electrolyte system (lithium hexafluorophosphate), compared with lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide has a higher lithium ion migration number (0.56 vs 0.38), that is, at the same rate, lithium bis(fluorosulfonyl)imide can reduce the concentration polarization of the electrolyte, improve the uniformity of the lithium insertion reaction in the thickness direction of the electrode, and reduce the risk of lithium precipitation; but considering the thermal stability, hygroscopicity, compatibility and other issues of lithium bis(fluorosulfonyl)imide, the inventors chose to use double salts. The additives used in the present invention can improve the intercalation kinetics of lithium ions, change the chemical composition and properties of the solid-liquid interface on the surface of the positive and negative electrodes, and are beneficial to the battery working under low temperature conditions. By studying the parameters such as the conductivity, viscosity, dielectric constant density, etc. of the electrolyte under different ratios, the appropriate additives are selected through experimental verification, and the appropriate electrolyte ratio and composition are determined. The conductivity of the electrolyte prepared by the present invention is always higher than that of ordinary electrolytes at low temperatures. After testing and verification of soft-pack batteries, it has excellent capacity retention and low-temperature cycle performance, which proves that the present invention has industrial production applicability.
[0027] The present application is further described in detail below with reference to the accompanying drawings and embodiments.
[0028] In the following examples of the present application, unless otherwise specified, the main components involved were purchased from commercially available products. Specific embodiments
[0030] Example 1
[0031] 30wt% of ethylene carbonate, 10wt% of ethyl methyl carbonate, 10wt% of dimethyl carbonate and 50wt% of ethyl propionate were mixed evenly in a glove box with a water and oxygen content of less than 0.3ppm, and then 1.1mol / L of lithium hexafluorophosphate was added. After the lithium salt was completely dissolved, 1.5wt% of vinylene carbonate was added, and the mixture was stirred and mixed evenly to obtain an electrolyte.
[0032] Example 2
[0033] 30wt% of ethylene carbonate, 10wt% of ethyl methyl carbonate, 10wt% of dimethyl carbonate and 50wt% of ethyl propionate were mixed evenly in a glove box with a water and oxygen content of less than 0.3ppm, and then 1.1mol / L of lithium bis(fluorosulfonyl)imide was added. After the lithium salt was completely dissolved, 1.5wt% of vinylene carbonate was added, and the mixture was stirred and mixed evenly to obtain an electrolyte.
[0034] Example 3
[0035] 30wt% of ethylene carbonate, 10wt% of ethyl methyl carbonate, 10wt% of dimethyl carbonate and 50wt% of ethyl propionate were mixed evenly in a glove box with a water and oxygen content of less than 0.3ppm, and then 0.55mol / L of lithium hexafluorophosphate and 0.55mol / L of lithium bis(fluorosulfonyl)imide were added. After the lithium salt was completely dissolved, 1.5wt% of vinylene carbonate was added, and the mixture was stirred and mixed evenly to obtain an electrolyte.
[0036] Example 4
[0037] 30wt% of ethylene carbonate, 10wt% of ethyl methyl carbonate, 10wt% of dimethyl carbonate and 50wt% of ethyl propionate were mixed evenly in a glove box with a water and oxygen content of less than 0.3ppm, and then 0.55mol / L of lithium hexafluorophosphate and 0.55mol / L of lithium bis(fluorosulfonyl)imide were added. After the lithium salt was completely dissolved, 1.5wt% of vinylene carbonate and 1.0wt% of fluoroethylene carbonate were added, and the mixture was stirred and mixed evenly to obtain an electrolyte.
[0038] Example 5
[0039] 30wt% of ethylene carbonate, 10wt% of ethyl methyl carbonate, 10wt% of dimethyl carbonate and 50wt% of ethyl propionate were mixed evenly in a glove box with a water and oxygen content of less than 0.3ppm, and then 0.55mol / L of lithium hexafluorophosphate and 0.55mol / L of lithium bis(fluorosulfonyl)imide were added. After the lithium salt was completely dissolved, 1.5wt% of vinylene carbonate, 1.0wt% of fluoroethylene carbonate and 0.5wt% of vinyl sulfate were added, and the mixture was stirred and mixed evenly to obtain an electrolyte.
[0040] Example 6
[0041] 30wt% of ethylene carbonate, 10wt% of ethyl methyl carbonate, 10wt% of dimethyl carbonate and 50wt% of ethyl propionate were mixed evenly in a glove box with a water and oxygen content of less than 0.3ppm, and then 0.55mol / L of lithium hexafluorophosphate and 0.55mol / L of lithium bis(fluorosulfonyl)imide were added. After the lithium salt was completely dissolved, 1.5wt% of vinylene carbonate, 1.0wt% of fluoroethylene carbonate and 0.5wt% of N,N-dimethyltrifluoroacetamide were added, and the mixture was stirred and mixed evenly to obtain an electrolyte.
[0042] Comparative Example 1
[0043] 30wt% of ethylene carbonate, 10wt% of ethyl methyl carbonate and 60wt% of dimethyl carbonate were mixed evenly in a glove box with a water and oxygen content of less than 0.3ppm, and then 1.1mol / L of lithium hexafluorophosphate was added. After the lithium salt was completely dissolved, 1.5wt% of vinylene carbonate was added, and the mixture was stirred and mixed evenly to obtain an electrolyte.
[0044] Comparative Example 2
[0045] 50 wt% of ethylene carbonate and 50 wt% of ethyl propionate were mixed evenly in a glove box with a water and oxygen content of less than 0.3 ppm, and then 1.1 mol / L of lithium hexafluorophosphate was added. After the lithium salt was completely dissolved, 1.5 wt% of vinylene carbonate was added, and the mixture was stirred and mixed evenly to obtain an electrolyte.
[0046] Comparative Example 3
[0047] 30 wt% of ethyl methyl carbonate, 20 wt% of dimethyl carbonate and 50 wt% of ethyl propionate were mixed evenly in a glove box with a water and oxygen content of less than 0.3 ppm, and then 1.1 mol / L of lithium hexafluorophosphate was added. After the lithium salt was completely dissolved, 1.5 wt% of vinylene carbonate was added, and the mixture was stirred and mixed evenly to obtain an electrolyte.
[0048] After testing, the conductivity of the electrolytes prepared in Examples 1 to 6 and Comparative Example 1 at different temperatures is as follows: Figure 1 shown.
[0049] Application Examples 1 to 6 and Comparative Application Examples 1 to 3 use the electrolytes prepared in the above Examples 1 to 6 and Comparative Examples 1 to 3 to produce 2Ah soft-pack batteries. Commercial lithium iron phosphate is selected as the positive electrode material, and graphite and hard carbon are mixed in a mass ratio of 1:1 as the negative electrode material; the capacity retention rate of the battery at different temperatures at a 1C discharge rate is tested respectively; the details are shown in Table 1.
[0050] Table 1
[0051]
[0052] It can be seen from Application Examples 1 to 6, Comparative Application Examples 1 to 3 and Table 1 that the three-component composite solvent (25 to 35 wt% of cyclic carbonate solvent, 15 to 25 wt% of linear carbonate solvent, and 45 to 55 wt% of carboxylate solvent) used in the technical solution of the present application can effectively improve the conductivity of the electrolyte, and the capacity retention rate of the prepared lithium-ion battery in a low temperature environment (0°C and below) is relatively high. This shows that the lithium-ion battery prepared by the technical solution of the present application has good energy storage performance in a low temperature environment.
[0053] It can be seen from Application Examples 1 to 2, Application Example 3 and Table 1 that the technical solution of this application adopts double salt (lithium hexafluorophosphate + lithium bis(fluorosulfonyl)imide) to replace the traditional single salt electrolyte system, which can effectively improve the energy storage performance of lithium ion batteries in low temperature environments below -20°C; therefore, in the technical solution of this application, the electrolyte using double salt is more suitable for lithium ion batteries operating in low temperature environments below -20°C.
[0054] It can be seen from Application Examples 3 to 5 and Table 1 that the additives composed of vinylene carbonate and fluoroethylene carbonate in a weight ratio of 3:2 and the additives composed of fluoroethylene carbonate, vinyl sulfate and vinyl sulfate in a weight ratio of 3:2:1 have higher capacity retention rate and better low temperature resistance in low temperature environment than the single additive of fluoroethylene carbonate.
[0055] It can be seen from Application Examples 3, 6 and Table 1 that the electrical performance of battery Application Example 6, which corresponds to the composite additive of vinylene carbonate, fluoroethylene carbonate and DTA in a weight ratio of 3:2:1, in a low-temperature environment is lower than that of battery Application Example 3, which corresponds to the single additive of fluoroethylene carbonate. Therefore, it is not the case that the low-temperature performance of the composite additive is higher than that of the single additive. It still depends on the components and ratios.
[0056] On the basis of Examples 3 and 4, the inventors further verified the effects of different addition amounts of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide in the double salt on the performance of the electrolyte in the technical solution of the present application; and made the following Examples 7 to 18, which are as follows.
[0057] Among them, Examples 7 to 12 are based on Example 3, except that only the addition amounts of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide are changed.
[0058] Example 7
[0059] 30wt% of ethylene carbonate, 10wt% of ethyl methyl carbonate, 10wt% of dimethyl carbonate and 50wt% of ethyl propionate were mixed evenly in a glove box with a water and oxygen content of less than 0.3ppm, and then 0.40mol / L of lithium hexafluorophosphate and 0.70mol / L of lithium bis(fluorosulfonyl)imide were added. After the lithium salt was completely dissolved, 1.5wt% of vinylene carbonate was added, and the mixture was stirred and mixed evenly to obtain an electrolyte.
[0060] Example 8
[0061] 30wt% of ethylene carbonate, 10wt% of ethyl methyl carbonate, 10wt% of dimethyl carbonate and 50wt% of ethyl propionate were mixed evenly in a glove box with a water and oxygen content of less than 0.3ppm, and then 0.45mol / L of lithium hexafluorophosphate and 0.65mol / L of lithium bis(fluorosulfonyl)imide were added. After the lithium salt was completely dissolved, 1.5wt% of vinylene carbonate was added, and the mixture was stirred and mixed evenly to obtain an electrolyte.
[0062] Example 9
[0063] 30wt% of ethylene carbonate, 10wt% of ethyl methyl carbonate, 10wt% of dimethyl carbonate and 50wt% of ethyl propionate were mixed evenly in a glove box with a water and oxygen content of less than 0.3ppm, and then 0.50mol / L of lithium hexafluorophosphate and 0.60mol / L of lithium bis(fluorosulfonyl)imide were added. After the lithium salt was completely dissolved, 1.5wt% of vinylene carbonate was added, and the mixture was stirred and mixed evenly to obtain an electrolyte.
[0064] Example 10
[0065] 30wt% of ethylene carbonate, 10wt% of ethyl methyl carbonate, 10wt% of dimethyl carbonate and 50wt% of ethyl propionate were mixed evenly in a glove box with a water and oxygen content of less than 0.3ppm, and then 0.60mol / L of lithium hexafluorophosphate and 0.50mol / L of lithium bis(fluorosulfonyl)imide were added. After the lithium salt was completely dissolved, 1.5wt% of vinylene carbonate was added, and the mixture was stirred and mixed evenly to obtain an electrolyte.
[0066] Embodiment 11
[0067] 30wt% of ethylene carbonate, 10wt% of ethyl methyl carbonate, 10wt% of dimethyl carbonate and 50wt% of ethyl propionate were mixed evenly in a glove box with a water and oxygen content of less than 0.3ppm, and then 0.65mol / L of lithium hexafluorophosphate and 0.45mol / L of lithium bis(fluorosulfonyl)imide were added. After the lithium salt was completely dissolved, 1.5wt% of vinylene carbonate was added, and the mixture was stirred and mixed evenly to obtain an electrolyte.
[0068] Example 12
[0069] 30wt% of ethylene carbonate, 10wt% of ethyl methyl carbonate, 10wt% of dimethyl carbonate and 50wt% of ethyl propionate were mixed evenly in a glove box with a water and oxygen content of less than 0.3ppm, and then 0.70mol / L of lithium hexafluorophosphate and 0.40mol / L of lithium bis(fluorosulfonyl)imide were added. After the lithium salt was completely dissolved, 1.5wt% of vinyl carbonate was added, and the mixture was stirred and mixed evenly to obtain an electrolyte.
[0070] Application Examples 7 to 12 The electrolyte prepared in the above Examples 7 to 12 was used to produce 2Ah soft-pack batteries. Commercial lithium iron phosphate was selected as the positive electrode material, and graphite and hard carbon were mixed in a mass ratio of 1:1 as the negative electrode material; the capacity retention rate of the battery at different temperatures under a 1C discharge rate was tested respectively; the details are shown in Table 2.
[0071] Table 2
[0072]
[0073] It can be seen from Application Examples 7 to 12 and Table 2 that in the technical solution of the present application, the weight ratio of lithium hexafluorophosphate to lithium bis(fluorosulfonyl)imide in the double salt is adjusted, when the weight ratio of lithium hexafluorophosphate is 4 / 11 to 7 / 11, and the weight ratio of lithium bis(fluorosulfonyl)imide is 4 / 11 to 7 / 11; the prepared battery has good low temperature resistance.
[0074] Among them, Examples 13 to 18 are based on Example 4, except that only the addition amounts of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide are changed.
[0075] Embodiment 13
[0076] 30wt% of ethylene carbonate, 10wt% of ethyl methyl carbonate, 10wt% of dimethyl carbonate and 50wt% of ethyl propionate were mixed evenly in a glove box with a water and oxygen content of less than 0.3ppm, and then 0.40mol / L of lithium hexafluorophosphate and 0.70mol / L of lithium bis(fluorosulfonyl)imide were added. After the lithium salt was completely dissolved, 1.5wt% of vinylene carbonate and 1.0wt% of fluoroethylene carbonate were added, and the mixture was stirred and mixed evenly to obtain an electrolyte.
[0077] Embodiment 14
[0078] 30wt% of ethylene carbonate, 10wt% of ethyl methyl carbonate, 10wt% of dimethyl carbonate and 50wt% of ethyl propionate were mixed evenly in a glove box with a water and oxygen content of less than 0.3ppm, and then 0.45mol / L of lithium hexafluorophosphate and 0.65mol / L of lithium bis(fluorosulfonyl)imide were added. After the lithium salt was completely dissolved, 1.5wt% of vinylene carbonate and 1.0wt% of fluoroethylene carbonate were added, and the mixture was stirred and mixed evenly to obtain an electrolyte.
[0079] Embodiment 15
[0080] 30wt% of ethylene carbonate, 10wt% of ethyl methyl carbonate, 10wt% of dimethyl carbonate and 50wt% of ethyl propionate were mixed evenly in a glove box with a water and oxygen content of less than 0.3ppm, and then 0.50mol / L of lithium hexafluorophosphate and 0.60mol / L of lithium bis(fluorosulfonyl)imide were added. After the lithium salt was completely dissolved, 1.5wt% of vinylene carbonate and 1.0wt% of fluoroethylene carbonate were added, and the mixture was stirred and mixed evenly to obtain an electrolyte.
[0081] Example 16
[0082] 30wt% of ethylene carbonate, 10wt% of ethyl methyl carbonate, 10wt% of dimethyl carbonate and 50wt% of ethyl propionate were mixed evenly in a glove box with a water and oxygen content of less than 0.3ppm, and then 0.60mol / L of lithium hexafluorophosphate and 0.50mol / L of lithium bis(fluorosulfonyl)imide were added. After the lithium salt was completely dissolved, 1.5wt% of vinylene carbonate and 1.0wt% of fluoroethylene carbonate were added, and the mixture was stirred and mixed evenly to obtain an electrolyte.
[0083] Embodiment 17
[0084] 30wt% of ethylene carbonate, 10wt% of ethyl methyl carbonate, 10wt% of dimethyl carbonate and 50wt% of ethyl propionate were mixed evenly in a glove box with a water and oxygen content of less than 0.3ppm, and then 0.65mol / L of lithium hexafluorophosphate and 0.45mol / L of lithium bis(fluorosulfonyl)imide were added. After the lithium salt was completely dissolved, 1.5wt% of vinylene carbonate and 1.0wt% of fluoroethylene carbonate were added, and the mixture was stirred and mixed evenly to obtain an electrolyte.
[0085] Embodiment 18
[0086] 30wt% of ethylene carbonate, 10wt% of ethyl methyl carbonate, 10wt% of dimethyl carbonate and 50wt% of ethyl propionate were mixed evenly in a glove box with a water and oxygen content of less than 0.3ppm, and then 0.70mol / L of lithium hexafluorophosphate and 0.40mol / L of lithium bis(fluorosulfonyl)imide were added. After the lithium salt was completely dissolved, 1.5wt% of vinylene carbonate and 1.0wt% of fluoroethylene carbonate were added, and the mixture was stirred and mixed evenly to obtain an electrolyte.
[0087] Application Examples 13 to 18 The electrolyte prepared in the above Examples 13 to 18 was used to produce 2Ah soft-pack batteries. Commercial lithium iron phosphate was selected as the positive electrode material, and graphite and hard carbon were mixed in a mass ratio of 1:1 as the negative electrode material; the capacity retention rate of the battery at different temperatures under a 1C discharge rate was tested respectively; the details are shown in Table 3.
[0088] Table 3
[0089]
[0090] It can be seen from Application Examples 13 to 18 and Table 3 that in the technical solution of the present application, by adjusting the weight proportion of lithium hexafluorophosphate in the double salt to 4 / 11 to 7 / 11, and the weight proportion of lithium bis(fluorosulfonyl)imide to 4 / 11 to 7 / 11, and then replacing the additive with a composite additive of fluoroethylene carbonate, vinyl sulfate and vinyl sulfate in a weight ratio of 3:2:1, the capacity retention rate of the battery at -10°C to 0°C can be improved, so that its electrical performance in this temperature range is better than that of the single salt electrolyte system; and in a low temperature environment of -40°C to -10°C, the capacity retention rate is higher and the electrical performance is better.
[0091] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A low temperature resistant electrolyte, characterized in that: including solvents and electrolytes; The solvent comprises 25-35 wt% of a cyclic carbonate solvent, 15-25 wt% of a chain carbonate solvent, and 45-55 wt% of a carboxylate solvent; The electrolyte comprises a lithium salt and an additive; wherein the lithium salt is one or a combination of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide, and the concentration of the lithium salt is 0.8-1.2 mol / L; wherein the content of the additive is 1-3 wt %.
2. The electrolyte according to claim 1, characterized in that The cyclic carbonate is one of ethylene carbonate and propylene carbonate or a combination of the two.
3. The electrolyte according to claim 1, characterized in that The chain carbonate is one or more of dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate and methyl propyl carbonate.
4. The electrolyte according to claim 1, characterized in that The carboxylic acid ester is ethyl propionate.
5. The electrolyte according to claim 1, characterized in that The lithium salt is a combination of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide.
6. The electrolyte according to claim 1, characterized in that In the lithium salt, the weight proportion of lithium hexafluorophosphate is 4 / 11 to 7 / 11, and the weight proportion of lithium bis(fluorosulfonyl)imide is 4 / 11 to 7 / 11.
7. The electrolyte according to claim 1, characterized in that The additive is one or more of vinylene carbonate, fluoroethylene carbonate, vinyl sulfate, and N,N-dimethyltrifluoroacetamide.
8. A method for preparing the electrolyte according to claim 1, characterized in that: According to the formula amount, the solvents are mixed evenly, and then the lithium salt is added in the formula amount. After the electrolyte is completely dissolved, the additives are added in the formula amount, and the mixture is stirred and mixed evenly to obtain an electrolyte.
9. The preparation method according to claim 8, characterized in that: The test was carried out in an environment where the water oxygen content was less than 0.3 ppm.
10. A lithium ion battery, characterized in that: The electrolyte described in claim 1 is used.